أثر المتغيرات الفردية على الرضا الوظيفي (دراسة آراء العاملين في جامعة دمشق) - بدر, ريم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى دراسة أثر المتغيرات الفردية في الرضا الوظيفي لدى العاملين في جامعة دمشق وتحديد مستوى الرضا الوظيفي للعاملين في الجامعة بشكلٍ عام، ولتحقيق الهدف من هذا البحث تم جمع البيانات اللازمة باستخدام أسلوب المعاينة العشوائية بوساطة استبيان تم تصميمه خصيصاً لهذا الغرض للتعرف على العوامل التي يكون العامل راضٍ عنها في العمل والعوامل التي يشعر نحوها بعدم الرضا، وبناءً على ذلك فقد توصلت الباحثة إلى أن مستوى الرضا الوظيفي للعاملين في جامعة دمشق مقبول بشكل ٍعام، وإلى عدم وجود فروق جوهرية في مستوى الرضا الوظيفي للعاملين في الجامعة وفقاً لعمر العامل، وأيضاً وفقاً لجنس العامل باستثناء عنصر الرضا عن زملاء العمل، ووفقاً للمستوى التعليمي باستثناء عناصر الرضا عن فرص الترقي وعن طبيعة العمل وعن العلاقة مع الرؤساء في العمل، وفي ضوء نتائج البحث قدمت الباحثة عدداً من التوصيات لتحسين درجة الرضا الوظيفي للعاملين في جامعة دمشق. The research aims at studying the influence of individual variables on job satisfaction of the staff at Damascus University, pinpointing also the level of job satisfaction of the staff at the University in general, to achieve this end, data has been collected by using random sampling and through a questionnaire which was designed especially for this purpose to know what aspects make the staff satisfied and what aspects make them dissatisfied, the researcher found out that the level of job satisfaction of the staff at Damascus University is acceptable In general, no major differences on the level of job satisfaction were found related to the employee's age, or employee's gender except in the field of satisfaction with the work colleagues. Also no major differences were found related to the education level, except for the satisfaction of promotion opportunities, nature of the work, and the relation with the boss. A number of recommendations have been developed to improve the level of staff's satisfaction in Damascus University.